Correlation between dmft, Diet and Social Factors in Primary School Children of Tehran-Iran in 2009-2010 - Mozhgan Faezi; Sareh Farhadi; Hossein NikKerdar (Mashhad University of Medical Sciences, 2012)
Introduction: One of the factors that can affect dental caries is the type of diet. So, this study was designed to evaluate the correlation between diet, social factors and dmft in primary school children of Tehran in 2009 and 2010.Materials & Methods: Eight handred and twenty primary school children of 6-12 years old (boys and girls) in Tehran were randomly selected in this descriptive study and after filling out the forms, underwent dental examinations. The data were analyzed by chi-square and logistic regression tests.Results: The Average dmft in school children was 2/9±1/81, which had a significant correlation with history of pain, dental visit and frequency of brushing (P=0.0281, 0.0119 and 0.0128), respectively, but there was no significant correlation between tendency for dental visit and dmft (P=0.831). Also, dmft was affected by history of pain, dental visit & frequency of brushing using regression values of 1.688, -0.893 & -0.593, respectively. There was a significant correlation between consumption of cariogenic diet and dmft. (P=0.0234) Number of siblings and mother's and father's educational stata also had significant correlations with dmft (P=0.0193, 0.0246, 0.0208 respectively). Number of siblings also had a significant relationship with cariogenic diet and mother's and father's educational stata had significant relationships with the type of diet, respectively (P=0.0319, 0.0257, 0.0197).Conclusion: Oral health care, history of pain and cariogenic type of diet had direct effect on the rate of dmft. Likewise, dmft increased with increase in the number of siblings and lower level of parents' educational status.